PENGARUH DIKLAT DAN PENGAWASAN TERHADAP KINERJA DENGAN KOMPETENSI PEGAWAI SEBAGAI INTERVENING DI KANTOR REGIONAL XII BADAN KEPEGAWAIAN NEGARA - Iswahyudi; Susi Hendriani; Yusni Maulida (Jurnal Economica, 2019)
The research held in Regional Office XII of National Civil Service Agency. The aim is to know the direct and indirect effect of Education & Training and Supervision toward competence and its implication to employee’s performance. Population are all employees of Regional Office XII of National Civil Service Agency. Census method was employed to determine the 80 employees as the sample. Data analysis tool is descriptive quantitative by using SEM-PLS.The study reveals that education & training has positive and significant effect towards competence and performance, while supervision, on the other hand, has negative but not significant towards competence and performance. Indirectly, competence partially mediates the relationship of education & training towards performance. However, competence is not a meditating factor for the relationship between supervision and performance.